2021
DOI: 10.31557/apjcp.2021.22.10.3245
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of FLT3 Internal Tandem Duplications in Adult Syrian Patients with Acute Myeloid Leukemia and Normal Karyotype

Abstract: Objective: Activating mutations of the fms-like tyrosine kinase 3 gene ( FLT3 ) by internal tandem duplications (ITDs) in the juxtamembrane domain (JMD) have been reported in ~30% of adult acute myeloid leukemia (AML) patients with cytogenetically normal karyotype (CN). However, FLT3 /ITD mutations are frequently accompanied with leukocytosis, high percentage of blasts in bone marrow (BM), and increased the risk of treatment failure in AML pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In FLT3-positive AML patients, mutations have been observed in the FLT3 gene on chromosome 13. The most prevalent of the FLT3 mutations is the internal tandem duplication (ITD) which is found in 15–30% of the AML patients [ 44 , 46 , 47 , 48 ]. The FLT3-ITD is an in-frame duplication in the juxtamembrane domain of the intracellular region of the FLT3 receptor ( Figure 2 ).…”
Section: The Choice Of Flt3 As Target For Car T-cell Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In FLT3-positive AML patients, mutations have been observed in the FLT3 gene on chromosome 13. The most prevalent of the FLT3 mutations is the internal tandem duplication (ITD) which is found in 15–30% of the AML patients [ 44 , 46 , 47 , 48 ]. The FLT3-ITD is an in-frame duplication in the juxtamembrane domain of the intracellular region of the FLT3 receptor ( Figure 2 ).…”
Section: The Choice Of Flt3 As Target For Car T-cell Therapymentioning
confidence: 99%
“…The second most prevalent FLT3 mutation is in the tyrosine kinase domain (TKD), which 5–10% of AML patients harbor [ 48 , 51 ]. The FLT3-ITD mutations are associated with reduced overall survival and are predictors of poor prognosis [ 43 , 46 , 51 , 52 ]. Thiede et al found that the risk of relapse was 1.6 with a median ratio (ITD/WT genotype) above 0.78 and poor overall survival, which is consistent with Whitman et al that found an overall survival rate of 74% for the FLT3 WT/WT genotype compared to 13% ( p = 0.008) for the FLT ITD/-genotype [ 48 , 53 ].…”
Section: The Choice Of Flt3 As Target For Car T-cell Therapymentioning
confidence: 99%
“…These mutations result in constitutive activation of FLT3 signaling, leading to aberrant proliferation, impaired differentiation, and increased survival of leukemic cells. FLT3 mutations are associated with adverse clinical features, including higher white blood cell counts, increased blast percentage, and a higher likelihood of relapse [ 5 ]. They have also been identified as independent prognostic factors for poor overall survival and decreased remission rates in AML patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%